Comparison of single- versus double-anastomosis duodenal switch: A single-center experience with 2-year follow-up. (1st June 2022) - Iranmanesh, P; Boudreau, V; Gmora, S; Hong, D; Anvari, M
Abstract: Objective: Single-anastomosis duodenal switch (SADS) has emerged in recent years as an alternative to the standard double-anastomosis duodenal switch (DADS). The objective of this study was to compare short- and medium-term outcomes between SADS and DADS. Methods: Data collected in the Ontario Bariatric Registry between 2010 and 2019 were used for this retrospective study to determine outcomes of patients undergoing primary laparoscopic SADS versus DADS at a Canadian tertiary hospital and bariatric center of excellence. The primary outcome was weight loss at 1 and 2 years after surgery. Short-term secondary outcomes included operative times, intra- and early postoperative complications, hospital length of stay (LOS), and 30-day readmissions. Medium-term secondary outcomes included late postoperative complications as well as nutritional deficiencies and persistent diarrhea at 1 and 2 years after surgery. Subgroup analyses were performed to compare patients undergoing one- and two-stage procedures. Results: Data of 107 patients who underwent SADS (n = 25) or DADS (n = 82) were included in the study. Follow-up data were available for 59/107 (55.1%) patients at 1 year and 47/107 (43.9%) at 2 years after surgery. Patients in the SADS and DADS groups had similar %TBWL at 1 year (23.6 versus 26.2, P = 0.617) and 2 years (24.8 versus 30.2, P = 0.116) after surgery. Short- and medium-term outcomes were similar between groups. There was no difference between patients undergoing one- versus two-stage procedures. Conclusion: This study showed that patients undergoing SADS and DADS had similar weight loss at 1 and 2 years. Early and late postoperative morbidity, operative times, early readmissions, and LOS were also similar between groups. Further studies with longer follow-up are required to confirm these results.